(untitled) (LACCEI, 2024)
The present research was carried out in Peru, comparing the budget of the multifamily project of a construction company with BIM and traditional methodology, for the realization of the article a non-experimental, descriptive design was used, considering as population and sample a multifamily project of Constructora Galilea with traditional and BIM methodology, data collection was carried out through the documentary review technique, the instrument used was the matrix of categories, to analyze the data used descriptive statistics, the problem arises from the budget of the multifamily project of Constructora Galilea which was prepared using traditional methodologies to be compared with the same budget but prepared using the BIM methodology in order to exploit its benefits such as the optimization of resources and costs, the budget prepared using the traditional methodology resulted in a total of S/. 1,238,541.36 while the budget elaborated using the BIM methodology was S/. 1,096,844.25, it was possible to compare the budget of the multifamily project of the Galilea construction company with BIM and traditional methodologies resulting in an optimization of 11.44% in costs in favor of the BIM methodology